Ministry of Trade and Industry Decree No. 135 of the year 2010 On Establishing the National Council for Industry Quality Assurance = وزارة التجارة والصناعة قرار رقم 135 لسنة 2010 بإنشاء المجلس القومى لضمان جودة الصناعة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.